The Effect of STEAM in Mathematics Learning on 21st Century Skills: A Systematic Literature Reviews - Pahmi, Samsul; Juandi, Dadang; Sugiarni, Rani (Universitas Suryakancana, 2022)
The development of a Science, Technology, Engineering, Art, and Mathematics (STEAM)-based learning approach that is implemented with interdisciplinary knowledge has now been widely used in learning and research in mathematics education. However, the use of learning methods and their influence on 21st century skills has not been fully described. To answer these problems, research is to investigate and interpret data on the development and use of appropriate methods in the implementation of STEAM, in particular its impact on mathematics learning and 21st century skills. The author conducted a systematic literature review of published articles to produce a bibliometric review that combines quantitative descriptions of literature content and qualitative analysis of processes, outcomes, and conditions of mathematics learning using the STEAM approach from selected databases between 2012 and 2021. The results of the study used 35 articles from literature relevant to the research objectives. After conducting the analysis, it can be concluded that research related to STEAM, especially in the study of mathematics, has increased significantly in the last 5 years since 2016. From the aspect of 21st century skills, STEAM has a dominant influence in improving problem solving skills and creativity. However, the impact of collaborative and communication skills is still low. In terms of the use of learning methods, STEAM has a significant relationship with the project-based learning (PjBL) method. The results of this study can be used as confirmation material showing that STEAM and PjBL methods are an ideal combination in learning and can also be used as alternative approaches and learning methods to improve problem solving and creative abilities.